Durability of pulmonary vein isolation for atrial fibrillation: a meta-analysis and systematic review - Teodor Serban; Diego Mannhart; Qurrat‐ul‐ain Abid; Andres Höchli; Sorin Lazar; Philipp Krisai; Arianna Sofia Bettelini; Sven Knecht; Michael Kühne; Christian Sticherling; Jeanne du Fay de Lavallaz; Patrick Badertscher (2023)
Abstract Aims Pulmonary vein isolation (PVI) plays a central role in the interventional treatment of atrial fibrillation (AF). Uncertainties remain about the durability of ablation lesions from different energy sources. We aimed to systematically review the durability of ablation lesions associated with various PVI-techniques using different energy sources for the treatment of AF. Methods and results Structured systematic database search for articles published between January 2010 and January 2023 reporting PVI-lesion durability as evaluated in the overall cohort through repeat invasive remapping during follow-up. Studies evaluating only a proportion of the initial cohort in redo procedures were excluded. A total of 19 studies investigating 1050 patients (mean age 60 years, 31% women, time to remap 2–7 months) were included. In a pooled analysis, 99.7% of the PVs and 99.4% of patients were successfully ablated at baseline and 75.5% of the PVs remained isolated and 51% of the patients had all PVs persistently isolated at follow-up across all energy sources. In a pooled analysis of the percentages of PVs durably isolated during follow-up, the estimates of RFA were the lowest of all energy sources at 71% (95% CI 69–73, 11 studies), but comparable with cryoballoon (79%, 95%CI 74–83, 3 studies). Higher durability percentages were reported in PVs ablated with laser-balloon (84%, 95%CI 78–89, one study) and PFA (87%, 95%CI 84–90, 2 studies). Conclusion We observed no significant difference in the durability of the ablation lesions of the four evaluated energies after adjusting for procedural and baseline populational characteristics.